2011
DOI: 10.1111/j.1365-2125.2011.03909.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic anaemia and abdominal pain – a cause not to be missed

Abstract: In January 2010, a 39-year-old Sri Lankan man, resident in Switzerland for 15 years, presented to the emergency department with constipation and abdominal pain from which he had suffered intermittently during the previous weeks. On physical examination, the abdomen was soft without tenderness or organomegaly. An abdominal X-ray confirmed stool retention without perforation or bowel obstruction. Laboratory testing revealed a haemoglobin level of 9.1 g dl -1 with normal indices and elevated reticulocytes.The blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A case report by Martin et al ( 28 ) of a 39-year-old Sri Lankan man, resident in Switzerland for 15 years, best describes the toxic effects of herbal products on blood and biochemical parameters. The patient presented to the emergency department with constipation and abdominal pain from which he had suffered intermittently during the previous weeks.…”
Section: Discussionmentioning
confidence: 99%
“…A case report by Martin et al ( 28 ) of a 39-year-old Sri Lankan man, resident in Switzerland for 15 years, best describes the toxic effects of herbal products on blood and biochemical parameters. The patient presented to the emergency department with constipation and abdominal pain from which he had suffered intermittently during the previous weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The instability of Hb Dompierre may explain the acute clinical manifestations observed in the present patient and the presence of some hemolytic biological features. Abdominal pain may be attributable to hemolytic crises, but is usually encountered in cases of massive intravascular hemolysis [10]. Despite the family history of abdominal pain on the maternal side, this does not seem to be associated with the Hb variant, which was not inherited from the mother.…”
Section: Case Reportmentioning
confidence: 96%
“…The patient underwent chelation therapy and has recovered clinically and biochemically [19]. In 2013, Muller et al reported Bhutanese traditional medicines was the rare cause of lead poisoning in Western countries [20].…”
Section: Case-2mentioning
confidence: 99%